Developing the i-spring media based on project based learning model on the alkane derivatives topic - Ratu Evina Dibyantini; Aura Fitriani Harahap (Jurnal Pendidikan Kimia (JPKim), 2022)
This study aims to (1) obtain i-spring-based media teaching materials from Project Based Learning which meet the criteria for content eligibility, language eligibility, and presentation eligibility under the National Education Standards Agency (BSNP), and (2) know the increase in student learning outcomes after using i-spring-based media Project Based Learning. The type of research used is Research and Development (R&D), which has been modified as needed. This research was conducted on students of class XII IPA 4 at Senior High School in Indonesia in the academic year 2021/2022, separately purposive sampling. The results showed that: 1) The developed i-spring-media based on Project Based Learning on the material of alkane derivative compounds meets the BSNP criteria, with the result: material feasibility is 3.31 and media feasibility is 3.51. It means the criteria are valid and do not need to be revised; 2) The developed media can improve student learning outcomes with an N-gain of 0.52 medium category.Keywords:Alkane derivatives, I-spring media, Project based learning